Acute Shock Liver in Inferior ST-Segment Elevation Myocardial infarct with Total Atrioventricular block: A Case Report - Mochamad Rizky Hendiperdana; Sumardjo Sumardjo (Acta Medica Indonesiana)
Liver dysfunction frequently accompanies heart diseases, especially in hemodynamically unstable acute heart failure or cardiogenic shock. This condition is marked by significant elevation of liver transaminases and brings high morbidity and mortality for > 50 % of cases. Despite the high mortality rate, early recognition with prompt management results in the recovery of liver function. A 53-year-old man presented with late-onset non-reperfused inferior STEMI. The patient presented with persistent chest pain and shortness of breath. The electrocardiogram showed atrioventricular (AV) block grade III and ST-segment elevation evolution in the inferior lead. The patient was diagnosed with a late-onset inferior STEMI with cardiogenic shock and total AV block complication, acute shock liver, lactic acidosis, and acute renal failure. We administered inotropic and chronotropic support drugs as well as post-MI anti-remodelling therapy to treat heart failure (HF) and left ventricular (LV) systolic dysfunction, such as angiotensin-converting enzyme inhibitor and aldosterone antagonist, after systemic perfusion improved. Anti-ischemic therapy, such as antithrombotics, was also administered. Renal and liver function test evaluation after a week of patient discharge showed normalization of these parameters. There is no definite treatment strategy for shock liver. The management strategy is directed at the treatment of underlying causes. Hemodynamic insult is the mainstay therapeutic target. Recovery of liver transaminases was demonstrated after the underlying insult had been eliminated.